A 13-year survey of pneumococcal nasopharyngeal carriage in children with acute otitis media following PCV7 and PCV13 implementation. Issue 39 (22nd September 2015) - Cohen, Robert; Varon, Emmanuelle; Doit, Catherine; Schlemmer, Catherine; Romain, Olivier; Thollot, Franck; Béchet, Stéphane; Bonacorsi, Stéphane; Levy, Corinne
Highlights During 13 years, Sp carriage was assessed annually for patients (>7900) with AOM. Before PCV7 period, PCV7 serotypes accounted for 45% and now they have disappeared. ST 19A increased from 9 to 16% before PCV13 implementation and decreased to 1% after. Predominant serotypes after PCV13 implementation were 15B/C, 11A, 15A, and 35B. Penicillin non-susceptible Sp decreased from 67% to 33% over 13 years.